Pendidikan Humanis antara Barat dan Islam - Telaah Kritis Pemikiran Pendidikan John Dewey - Saleh, Khairul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2012)
Humanistic education conceptually has three paradigms of contemporary education thought. They are; progressivism, constructivism, and existentialism. Actually, if they are deeply explored, they can be found in the basic of Islamic education. Islamic education which is based on Qur’an and hadits is required to develop based on the situations, conditions, and problems which always develop as well. Referring to the flow of the legitimative-pragmative thought, those three paradigms can be used as a reference to create a new paradigm (not in absolute manner) in developing Islamic education which sometimes in the practice still tend to develop from normative-conservative into normative-pragmative contemporary paradigm.